2023
DOI: 10.1002/bkcs.12776
|View full text |Cite
|
Sign up to set email alerts
|

Predicting photoresist sensitivity using machine learning

Balaji G. Ghule,
Minkyeong Kim,
Ji‐Hyun Jang

Abstract: We introduce a scheme for predicting photoresist sensitivity using machine learning (ML) work flow on the basis of previously reported experimental data. Different ML models, specifically Linear Regression, Kernel Ridge Regression, Gaussian Process Regressor, Random Forest Regressor, and Multilayer Perceptron Regressor, were evaluated to rapidly identify the best sensitivity prediction model. The experiment was carried out on the Google Colab platform using the Materials Simulation Toolkit for Machine Learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…102 It has been applied to various research fields such as polymer materials, 103 molecular structure predictions, 104 perovskite structure predictions, 105 and new medicine developments. 106,107 Experimental and theoretical studies on phonon scattering, defect engineering, band structure modulation, and heterogeneous structure formation by doping and alloying have provided effective strategies to improve TE properties of materials. ML can be a useful tool to predict new TE materials with optimal compositions and may help save time and labor.…”
Section: Prediction Of High-performance Snse Te Materials By Machine ...mentioning
confidence: 99%
“…102 It has been applied to various research fields such as polymer materials, 103 molecular structure predictions, 104 perovskite structure predictions, 105 and new medicine developments. 106,107 Experimental and theoretical studies on phonon scattering, defect engineering, band structure modulation, and heterogeneous structure formation by doping and alloying have provided effective strategies to improve TE properties of materials. ML can be a useful tool to predict new TE materials with optimal compositions and may help save time and labor.…”
Section: Prediction Of High-performance Snse Te Materials By Machine ...mentioning
confidence: 99%
“…Machine learning (ML) has been recently utilized for the analysis of MPs in various matrices, as it is in the other analytical issues, such as mass spectrometry 38–42 . Ng et al, demonstrated that a 1D‐convolution neural network (1D‐CNN) model can screen the degree of MP contaminations for soils that were contained with polyethylene terephthalate (PET) or low‐density polyethylene (LDPE) mixtures using visible–near infrared spectra 43 .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Therefore, machine learning (ML) approaches to screen numerous BHJ combinations in a short time and with little effort, based on a comprehensive understanding of the potential of OPV materials, have attracted considerable attention. 15,16 State-of-the-art OPV ML models achieved superior accuracy with a variety of input data types and algorithms. [17][18][19][20] However, the training of previous OPV ML models and obtaining predictions from them required at least one chemical property that could only be determined through experiment or calculation.…”
Section: Introductionmentioning
confidence: 99%